Role of Bis(triphenylphosphine)iminium Cation [PNP]+ on the Crystal Packing of [PNP]+[HSeO3]− Solvate Salt - Stefano Canossa; Claudia Graiff (Crystals, 2018)
Selenate(IV) and hydrogen selenate(IV) salts of bulky cations are very interesting compounds for synthetic and kinetic studies. In this work, bis(triphenylphosphine)iminium ([PNP]+) chloride has been used, which aims to synthesize the corresponding selenate(IV) salt by an exchange reaction in the aqueous solution and subsequent crystallization by solvent evaporation. Unexpectedly, the procedure afforded a solvate form of the [PNP]+[HSeO3]− salt (1). In this solid phase, which has a structure that is determined by Single Crystal XRD, the anion tends to maximize the interactions with itself, although it leaves the cationic moiety to have only weak interactions with the anions and the solvent molecules. In turn, the latter builds a network of effective hydrogen bonds. This behavior opposes the general tendency of selenite(IV) and hydrogen selenite(IV) compounds, since these anions are commonly found to have formed effective hydrogen bonds with surrounding chemical species. Moreover, as the exchange reaction is non-quantitative, the exceeding traces of the starting bis(triphenylphosphine)iminium chloride reagent reacted with bis(acetonitrile)dichloropalladium(II) to form the bis(triphenylphosphine)iminium hexachloropalladate (2). In the solid phase, [PNP]+ causes the absence of strong supramolecular interactions, which highlights the peculiar behavior of the cation in the crystal packing of its solid phases.